Unveiling the Dimensionality of Pricing Strategy in the Tourism Industry: An Exploratory Factor Analysis - Tiwari, Ghanashyam (Journal of Interdisciplinary Studies, 2024)
Tourism is a dynamic and ever-changing industry that plays a significant role in the global economy. As competition intensifies, tourist firms must design effective pricing strategies to attract and retain clients. The objective of the study is to explore the most influencing pricing strategies in the tourism business. A structured questionnaire was developed to discover the price strategy of various tourism enterprises in the Gandaki Province of Nepal. Exploratory factor analysis entails several stages to uncover these hidden components. Factors with eigenvalues greater than one are considered significant to confirm the constructs. Among five construct variables, competition-based pricing explains the highest variance and is followed by a customer-centric pricing strategy. This study provides significant insights into tourism industries’ sustainable competitive advantages.